(untitled) - Elliott, David (New York, 2003)
Whilst energy use is fundamental to human existence, it is also at the heart of many environmental problems we face in the 21st century. Deteriorating air quality and the global warming phenomenon can all be attributed to our use of fossil fuels. The re-emergence of nuclear power as an alternative also prompts major concerns. Sustainable alternatives such as wind and hydroelectric power also face opposition.
Keywords: Nguồn điện,Power resources; Khía cạnh môi trường,Environmental aspects